Creating a culture of predictable outcomes : how leadership, collaboration, and decision-making drive architecture and construction - Bryson, Barbara White (New York, NY : Routledge, 2021)
"Creating a Culture of Predictable Outcomes demonstrates the importance of creating cultures in the design and construction industries grounded in sophisticated, caring leadership, high-performing collaborative teams, and master-level decision-making discipline, informed by values, to finally address massive inefficiencies, waste, and unpredictability. Barbara White Bryson offers specific guidance to industry stakeholders to succeed in achieving project-related predictable outcomes by focusing on culture rather than process. This includes selecting the right team members by hiring and firing bravely, valuing psychological safety, leading with values, practicing respect and transparency, fostering empowerment to make decisions at the right level at the right time, and more. This book is a must-read for design and construction professionals who want to finally understand how to set goals and meet those goals for their clients as well as for their teams"--
OCLC-licensed vendor bibliographic record.
Keywords: Building -- Superintendence; Design-build process (Construction industry); Architectural practice; Corporate culture; ARCHITECTURE / General; ARCHITECTURE / Professional Practice; ARCHITECTURE / Project Management